1994
DOI: 10.1038/bjc.1994.187
|View full text |Cite
|
Sign up to set email alerts
|

Dose finding study of granisetron in patients receiving high-dose cisplatin chemotherapy

Abstract: Summary The efficacy and safety of three different doses of granisetron (2pjgkg-', group A; 10;Lgkg-', group B; 40jiygkg-', group C) were compared in a randomised, double-blind study of 157 patients due to receive high-dose cisplatin therapy (mean dose >97 mg m-2). In each group, up to two 3 mg rescue doses of granisetron were allowed if more than mild nausea or vomiting occurred. In group A 30.8%, in group B 61.5% and in group C 67.9% of patients were complete responders (i.e. no vomiting or nothing worse tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0
1

Year Published

1996
1996
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(17 citation statements)
references
References 8 publications
2
14
0
1
Order By: Relevance
“…[29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45] For the 2017 update, the NCCN panel added recommendations for a new formulation of granisetron-subcutaneous granisetron extended-release injection-in antiemetic regimens for HEC and MEC based on published data and recent FDA approval (see AE-5, AE-6, AE-7, and AE-A 2; pages 886-888 and 890). It is important to note that subcutaneous granisetron extended-release injection is a unique formulation of granisetron using a polymer-based drug delivery system.…”
Section: Granisetronmentioning
confidence: 99%
“…[29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45] For the 2017 update, the NCCN panel added recommendations for a new formulation of granisetron-subcutaneous granisetron extended-release injection-in antiemetic regimens for HEC and MEC based on published data and recent FDA approval (see AE-5, AE-6, AE-7, and AE-A 2; pages 886-888 and 890). It is important to note that subcutaneous granisetron extended-release injection is a unique formulation of granisetron using a polymer-based drug delivery system.…”
Section: Granisetronmentioning
confidence: 99%
“…[10][11][12][13] The combination of a 5-HT3 receptor antagonist and a corticosteroid represent the current standard of care in the prevention of emesis with moderate to highly emetogenic chemotherapy. 19 For patients receiving high-dose chemotherapy or chemo/ radiotherapy regimens in association with hematopoietic stem cell support, a number of studies suggest that antiemetic control may be a greater challenge in this setting.…”
Section: Discussionmentioning
confidence: 99%
“…The use of 5-hydroxytryptamine-3 (5HT3) antagonists, such as dolasetron, granisetron and ondansetron, have contributed significantly to the control of nausea and vomiting in patients receiving moderately and highly emetogenic chemotherapy. [10][11][12][13] The great majority of patients receiving emetogenic chemotherapy at standard doses should achieve complete control of emesis at the present time.A number of patient and treatment-related factors predictive for the development of chemotherapy-induced emesis have been defined. These include age, gender, ethanol consumption history, and the intrinsic emetogenicity of the chemotherapy agents.…”
mentioning
confidence: 99%
“…The dried formulation films were carefully cut into uniform sizes to contain a theoretical equivalent of ∼4 mg of the drug per film. This dose of GRN (4 mg per film) was targeted based on the recommended therapeutic doses of GRN for chemotherapy-induced nausea and vomiting (24). Preliminary studies based on film dimensions showed that GRN (9.1% w/w) in the formulations achieved this target dose per film.…”
Section: Preparation and Characterization Of Granisetron Transdermal mentioning
confidence: 99%